Pengaruh Fraksi Udara Terhadap Koefisien Perpindahan Kalor Kondensasi Refrigeran Petrozon Rossy-22 Di Dalam Pipa Tegak - Sudarja Sudarja; Purnomo Purnomo; Prajitno Prajitno (Universitas Muhammadiyah Yogyakarta, 2007)
Petrozon Rossy-22 is one of hydrocarbon refrigerants which environmentally safe, since there is no effect on either ozone depletion or global warming. In the refrigeration cycle, imperfect vacuuming process or other factors that permit circulation of air taken place in the system predicted influencing heat transfer rate in condenser. Therefore, research on the influence of air fraction against condensation heat transfer coefficient of Petrozon Rossy-22 inside vertical pipe to be done. A modified refrigeration system of vapor compression was applied in this research, where the condensation was done in the 2 meters straight vertical condenser (double pipe heat exchanger, that further called as test section). The diameter of internal and external pipe were ¾” and 1 ¼” respectively. Electric heater was installed on upstream of the test section. Mixture of air- refrigerant was flowed downward inside internal pipe, while cooling water was flowed upward through annulus. The varied parameters were: air fraction, air-refrigerant and cooling water flow rate. The result of the research indicated that condensation heat transfer coefficient significantly decreased when air fraction increased. The proposed empiric equation is : Nu = 0.0138. (1-w)8.8198. Re0.7941. Pr4.7315with determination coefficient of 0.6927 and average absolute deviation of 17.65 %. The equation was for Re= 6.922-12.953, Pr= 2,008-2,696, and w= (0,25-1)%.